Purification, identification, and in silico screening of a multifunctional octapeptide from semen armeniacae glutelin-2 hydrolysates: restraining mechanisms to Keap1 and ACE, stability, and ferrous-transport efficiency - Jin, Ziqing; Dang, Ling; Li, Yan; Feng, Chen; Song, Xinling; Wei, Zhihui; Liu, Jie; Wang, Hao; Zhang, Yichan (Frontiers in Nutrition, 2025)
IntroductionSemen armeniacae is a traditional homologous material of medicine and food, but data on its multifunctional peptides are little.MethodsIn this study, semen armeniacae glutelin-2 was hydrolyzed by alcalase and trypsin assisted with ultrasound. Antihypertensive and antioxidant peptides with ferrous-binding activity were isolated, identified, and in silico screened from the hydrolysates, and the action mechanisms against Keap1 and angiotensin-I-converting enzyme (ACE), gastrointestinal stability, and ferrous-binding capacity were studied.Results and discussionAfter Sephadex G-15 isolation, electrospray ionization mass spectrometry, and AHTpin and Peptide Ranker database screening, a safe multifunctional octapeptide: Pro-Val-Asp-Phe-Ala-Gly-Phe-Tyr (PVDFAGFY), was obtained. The capacities of PVDFAGFY to restrain ACE, chelate ferrous ions, and quench hydroxyl radical were IC50:105.61 μmol/L, 11.67 mg/g, and 97.67%, respectively. PVDFAGFY restrained ACE via competitively linking to its catalytic (His383) and/or crucial binding sites (Gln281, Lys511, Tyr523, Tyr520, or Ala354), and it can inhibit the Keap1-Nrf2 interaction by binding to 6 residues of Keap1. Ferrous ions were primarily chelated by γ-hydroxyl, carboxyl, and/or amino groups of PVDFAGFY via ionic forces. Gastrointestinal hydrolysis did not decrease the capacity of PVDFAGFY to antioxidant and restrain ACE (p > 0.05). The ACE inhibition model and activity of PVDFAGFY were not altered by iron chelation; however, PVDFAGFY-ferrous chelate showed lower hydroxyl and ABTS radical quenching capacity and ferric reducing ability than PVDFAGFY (p < 0.05). The gastrointestinal stability and transmembrane absorption of ferrous ions were increased by PVDFAGFY (p < 0.05). Thus, PVDFAGFY may be exploited as ingredients of hypotensive, antioxidant, and/or iron supplementary agents, but in vivo antioxidant and hypotensive efficiencies need further study.